2016
DOI: 10.1103/physrevb.94.174440
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance generated from charge-spin conversion by anomalous Hall effect in metallic ferromagnetic/nonmagnetic bilayers

Abstract: A theoretical formulation of magnetoresistance effect in a metallic ferromagnetic/nonmagnetic bilayer originated from the charge-spin conversion by the anomalous Hall effect is presented. Analytical expressions of the longitudinal and transverse resistivities in both nonmagnet and ferromagnet are obtained by solving the spin diffusion equation. The magnetoresistance generated from charge-spin conversion purely caused by the anomalous Hall effect in the ferromagnet is found to be proportional to the square of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We found that the ADMR results observed for our Fe films can be well explained by AHMR. Including the conventional AMR effect [2][3][4][5], GSE [17][18][19], and the AHMR effect [14][15][16] gives a general MR form of…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the ADMR results observed for our Fe films can be well explained by AHMR. Including the conventional AMR effect [2][3][4][5], GSE [17][18][19], and the AHMR effect [14][15][16] gives a general MR form of…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the discovery of several types of MR effects with different origins has triggered renewed interest in spin-dependent MR. These MR effects include spin Hall magnetoresistance (SMR) in FM/heavy metal bilayers [6][7][8], Rashba-Edelstein magnetoresistance (REMR) in Bi/Ag/CoFeB [9], spin-orbit magnetoresistance (SOT-MR) in a YIG/Pt/Cu system [10], Hanle magnetoresistance (HMR) in HMs [11], anisotropic interfacial magnetoresistance (AIMR) in Pt/Co/Pt [12,13], and anomalous Hall MR (AHMR) in single FM layers [14][15][16]. In a particular magnetic system, several types of MR could coexist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pure spin Hall angle in the nonmagnet and the spin polarization of the conductivity in the ferromagnet are ϑ and β, respectively. The quantity g * is related to the F/N interface resistance, whereas g N /S with the F/N cross section area S is defined as g N /S = hσ N /(2e 2 λ N ) [30]. The origin of the z axis locates at the F/N interface.…”
Section: System Descriptionmentioning
confidence: 99%
“…where m k = (m kx , m ky , m kz ) is the unit vector pointing in the magnetization direction in the F k layer. The dimensionless coefficients, χ and χ ′ , in metallic ferromagnetic/nonmagnetic bilayers are given by [27,29,30]…”
Section: Llg Equationmentioning
confidence: 99%